A ambiência pedagógica digital: aprendizagem da docência e coreografias didáticas digitais na educação básica - Eidelwein, Luciana Patricia Schumacher (2016)
This master‟s thesis is part of LP1 Formation, Knowledge and Professional Development research line from the Graduate Program in Education of the Federal University of Santa Maria, aiming at understanding the influences of digital pedagogical ambience in learning of teaching and in the production of digital didactic choreographies of elementary school teachers. The master‟s thesis unfolds in the following specific objectives: a) to know the configuration of digital pedagogical ambience in the context of first years of elementary school in a basic education school; b) to identify how teachers organize their pedagogical practices using digital technologies; c) to recognize how teachers manifest technological pedagogical knowledge. This study adopts a qualitative approach of sociocultural nature as its methodology, with narrative interviews, contributing to the elucidation of the proposed theme. Results demonstrate that the school researched is promoting a digital pedagogical ambience through a computer laboratory, properly maintained and available to all teachers and students; teaching training about the operational system LINUX and tools and applications; assistance and guidance from a technologically fluent teacher, who is responsible for the laboratory; and that this space is already part of the school culture. Teachers redefied themselves through reflections on their practices, sharing with peers and through the appropriation of technological pedagogical knowledge. Therewith, they include activities involving technology in their pedagogical practices, making the identification development of the four levels of didactic choreographies possible: anticipation, scene placement, learning basic model and student learning product.